TSSB için Bilişsel Davranışçı Başa Çıkma Becerileri Çalışma Kitabı - Eğeci, Sine; Karabulut, Goncagül; Göktürk Duru, Berçem; Şeker, Zeynep; Koçer, Duygu; Akekmekçi Tunalı, Hilal; Erk, Mehmet Aykut; Erkol, Ecem; Bahşi, Alagün Belce; Dikmen, Cansu; Demircioğlu, Melis (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-